The current status and evolution of hemodialysis catheters - Chen, Kanan; Liu, Xiaomei; Luo, Qun; Cai, Kedan (Renal failure, 2025)
Chronic kidney disease (CKD) represents a growing global health burden, with an increasing number of CKD patients progressing to renal failure or end-stage renal disease (ESRD). Hemodialysis is widely regarded as the usual treatment modality for patients with ESRD. Currently, more than 85% of patients initiating hemodialysis (HD) in the United States utilize a catheter for vascular access. HD is often inseparable from the use of catheters in clinical practice. Consequently, the utilization of HD catheters has risen, despite their associated complications and adverse outcomes. To minimize complications during dialysis sessions, various strategies are employed, including optimized catheter designs, specialized catheter lock solutions or functional coatings, and effective catheter care. This review outlined the current state and development of HD catheters, along with the associated adverse outcomes and effective care strategies.